The Impact of Maternal Obesity on NICU and Newborn Nursery Costs - Azher, Sharmeen; Pinheiro, Joaquim M. B.; Philbin, Brendan; Gifford, Jamie; Khalak, Rubia (Frontiers in Pediatrics, 2022)
Background Research on the effects of maternal obesity on neonates has focused on clinical outcomes. Despite growing interest in obesity as a driver of healthcare expenditure, the financial impact of maternal obesity in the neonatal setting is little understood. Objective To determine if maternal obesity is associated with higher incurred costs in NICU and full-term nursery. Methods Data for all live births (1/1/14–12/31/19) at our academic medical center was obtained from the New York State Perinatal Data System for infants >23 weeks gestational age. Financial data was obtained from the hospital's cost-processing application. Infants with missing clinical and/or financial data were excluded. The NIH definition of obesity was used (BMI ≥ 30 kg/m2) to separate infants born to obese and non-obese mothers. Student's t-tests and chi square tests were used to compare maternal data, delivery, and infant outcomes between both groups. A logistic regression model was used to compare infant outcomes using odds ratios while controlling for maternal risk factors (smoking status, pre-pregnancy and gestational diabetes, pre-pregnancy and gestational hypertension). Multivariate regression analysis adjusting for maternal risk factors was also used to compare length-of-stay, total and direct costs in the NICU and full-term nursery between infant groups. Results Of the 11,610 pregnancies in this retrospective study, obese mothers more frequently had other risk factors (smoke, pre-pregnancy and gestational diabetes, and pre-pregnancy and gestational hypertension). Infants born to obese mothers were more often preterm, had Cesarean delivery, lower APGAR scores, required assisted ventilation in the delivery room, and required NICU admission. Adjusting for maternal risk factors, infants born to obese mothers were less frequently preterm (OR 0.82 [0.74–0.91], p < 0.01) and had NICU stays (OR 0.98 [0.81–0.98], p = 0.02), but more frequently had Cesarean births (OR 1.54 [1.42–1.67], p < 0.01). They also had longer adjusted LOS (2.03 ± 1.51 vs. 1.92 ± 1.45 days, p < 0.01) and higher mean costs per infant in the full-term nursery ($3,638.34 ± $6,316.69 vs. $3,375.04 ± $4,994.18, p = 0.03) but not in NICU. Conclusions Maternal obesity correlates with other risk factors. Prolonged maternal stay may explain increased LOS and costs in the full-term nursery for infants born to obese mothers, as infants wait to be discharged with mothers.